La psicología y las incertidumbres y temores de la nueva guerra fría - León, Ramón (2025)
Following the war between Russia and Ukraine and the shift in American foreign policy since thestart of Donald Trump’s administration, there is increasing talk of the beginning of a new “ColdWar.” Considering history regarding the “First Cold War” (1945-1990), this paper attempts topresent the prevailing sentiments at this time regarding the uncertainty of humanity’s future, also analyzing the role that psychology can play in a situation like the one we are experiencing today.